In-bore MRI targeted biopsy - Gurgitano, Martina; Ancona, Eleonora; Maresca, Duilia; Summers, Paul Eugene; Alessi, Sarah; Maggioni, Roberta; Liguori, Alessandro; Pandolfi, Marco; Rodà, Giovanni Maria; De Filippo, Massimo; Paolucci, Aldo; Petralia, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Clinical suspicion of Prostate Cancer (PCa) is largely based on increased prostate specific antigen (PSA) level and/or abnormal digital rectal examination (DRE) and/or positive imaging and, up today, biopsy is mandatory to confirm the diagnosis. The old model consisted of Standard Biopsy (SBx), that is random sampling of the prostate gland under ultrasound guidance (TRUS), in subjects with clinical suspicion of PCa. This involves the risk of not diagnosing a high percentage of tumors (up to 30%) and of an incorrect risk stratification. Multiparametric Magnetic Resonance Imaging (mpMRI) has transformed the diagnostic pathway of PCa, not only as an imaging method for detecting suspicious lesions, but also as an intraprocedural guidance for Target Biopsy (MRI-TBx), thus bridging the diagnostic gap. Several single and multicenter randomized trials, such as PROMIS, MRI first, PRECISION and that reported by Van der Leest et al. have confirmed the superiority of the “MRI pathway”, consisting of mpMRI and MRI-TBx of suspicious lesions, over the “standard pathway” of SBx in all patients with elevated PSA and/or positive DRE. MRI-TBx appears to be advantageous in reducing the overall number of biopsies performed, as well as in reducing the diagnosis of clinically insignificant disease while maintaining or improving the diagnosis of clinically significant PCa (cs-PCa). Moreover, it shows a reduction in the diagnosis of ins-PCa, and therefore, of overdiagnosis, when using MRI-TBx without sacrificing performance in the diagnosis of cs-PCa.